-9d-19=-11d+19

Simple and best practice solution for -9d-19=-11d+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9d-19=-11d+19 equation:


Simplifying
-9d + -19 = -11d + 19

Reorder the terms:
-19 + -9d = -11d + 19

Reorder the terms:
-19 + -9d = 19 + -11d

Solving
-19 + -9d = 19 + -11d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '11d' to each side of the equation.
-19 + -9d + 11d = 19 + -11d + 11d

Combine like terms: -9d + 11d = 2d
-19 + 2d = 19 + -11d + 11d

Combine like terms: -11d + 11d = 0
-19 + 2d = 19 + 0
-19 + 2d = 19

Add '19' to each side of the equation.
-19 + 19 + 2d = 19 + 19

Combine like terms: -19 + 19 = 0
0 + 2d = 19 + 19
2d = 19 + 19

Combine like terms: 19 + 19 = 38
2d = 38

Divide each side by '2'.
d = 19

Simplifying
d = 19

See similar equations:

| x^2+y^2-6x-16y+57=0 | | yx+6y=7 | | 300+20x=500+12y | | 16-0.3(m-13)=0.4(5m-13) | | r^2-20rs-44s^2=0 | | 4(2x-1)=-100 | | 3(1+4n)-3(5n-3)=25 | | 5-0.1(d-2)=0.5(5d-2) | | 3(x+1)-(3x+2)= | | -15(x-38)=x+(-44) | | (3x^2+4x)(15x^2-7x-4)=0 | | n=0.733(7)+8.398 | | 5-(4-1+2*1)= | | 4+1/3x=-5 | | 5-(4-0+2*0)= | | n=0.733(9)+8.398 | | 1.66666x=15 | | -9w+3-7+6w= | | 7/9x=21 | | 2x^2+18x-1944=0 | | 23.1=3.3n | | 2/w-1=-9-(4/w-2) | | 2x^2-5x-120=0 | | 1/13x^2 | | 4x-(25-x)=85 | | -2y1/3 | | 3x+16=240 | | 25x-30=4(5x-6)+5x-6 | | 8x+2(3x-12)=-122 | | 21.3=3.3n | | .33h-4(.66h-3)=.66h-6 | | b-4+8b=24 |

Equations solver categories